EVALUATING THE USE OF MCQ AS AN ASSESSMENT METHOD IN A MEDICAL SCHOOL FOR ASSESSING MEDICAL STUDENTS IN THE COMPETENCE-BASED CURRICULUM - Mitayani Purwoko; Trisnawati Mundijo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Student’s cognitive ability could be assessed using MCQ. The aim of this study was to evaluate the quality of MCQ as an assessment method in Medical Faculty of Muhammadiyah University Palembang. Method: This study was designed as a cross sectional descriptive observational study. Sample was MCQ assessment in Genetics and Molecular Biology Module for academic year 2013/2014 until 2015/2016 for total 299 questions. Item analysis was done manually.Results: The item analysis showed that 61.2% questions were recall-type question. This situation showed that the construction of the question was not good and only testing the lower cognitive area. There was 45.2% ideal question with 30-70% difficulty index and 23.1% questions whom distractor efficiency was 100%. Half of the questions (56.2%) should  be revised. This revision-needed questions distributed equally into easy, ideal, and hard level of difficulty. Revision-needed questions had lower distractor efficiency mean compared to good questions. Conclusion: MCQ as an assessment method do not reach maximum target yet because there were many questions that should be revised. Faculty should enhance the development of the lecturer in writing the good MCQs.